2018
DOI: 10.3390/v10060291
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of the CRISPR/Cas9 System against Herpesvirus Infections

Abstract: The CRISPR/Cas9 system has been applied in the genome editing and disruption of latent infections for herpesviruses such as the herpes simplex virus, Epstein–Barr virus, cytomegalovirus, and Kaposi’s sarcoma-associated herpesvirus. CRISPR/Cas9-directed mutagenesis can introduce similar types of mutations to the viral genome as can bacterial artificial chromosome recombination engineering, which maintains and reconstitutes the viral genome successfully. The cleavage mediated by CRISPR/Cas9 enables the manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 40 publications
0
51
0
3
Order By: Relevance
“…Numerous studies showed successful use of CRISPR/Cas9 in genetic studies of herpesviruses. However, as of today, there is no report on genetic engineering of KSHV genome in PEL cells by CRISPR/Cas9 (13,14).…”
mentioning
confidence: 99%
“…Numerous studies showed successful use of CRISPR/Cas9 in genetic studies of herpesviruses. However, as of today, there is no report on genetic engineering of KSHV genome in PEL cells by CRISPR/Cas9 (13,14).…”
mentioning
confidence: 99%
“…The viral capsid decomposes to release viral DNA genome to manipulates host enzyme systems to make new virions. During symptomatic infection, infected cells express lytic genes to demonstrate a lytic pathway [12]. Nevertheless, instead of this, some viral genes may transcribe latency associated transcripts to accumulate in host cells.…”
Section: Life Cyclementioning
confidence: 99%
“…For the lysogenic pathway, the viruses are persistent in the host, not causing any adverse reactions, but can be transmitted to other hosts by direct contact. When CMV are stimulated by explanation or their host immune system is suppressed, the dormant viruses can reactivate to begin generating large number of viral progenies to cause symptoms and diseases, described as the lytic life cycle [12,13].…”
Section: Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Herpesviruses are nuclear-replicating DNA viruses with large dsDNA genomes (100-200 kb) that encode 100 to 200 genes (8). They frequently undergo homologous recombination during their replication cycle and can be efficiently edited by CRISPR-Cas9 (9)(10)(11)(12). These properties enabled the design of a new gene drive strategy that doesn't involve sexual reproduction, but relies on coinfection of a given cell by a wildtype and an engineered virus ( Fig.…”
Section: Main Textmentioning
confidence: 99%